Strategi Penanggulangan Penularan penyakit Hiv/Aids ( Kajian Sosiologis Pada Masyarakat Ujung Tanah Kota Makassar) - Wahyuddin Wahyuddin; Sam'un Mukramin (KOLONI, 2023)
At present the number of detection and treatment of PLWHA in the province of South Sulawesi ranks 7th nationally. become a phenomenon that must immediately get attention, including what happened to residents of Ujung Tanah sub-district in Makassar City, in this case we carried out a qualitative method with descriptive research. The purpose of this research is to provide an understanding to every young person about the dangers of infectious diseases and the dangers of disease transmission HIV / AIDS, which until now has not found a suitable drug for the disease.  Keywords: youth, campaigns, free sex, HIV/AIDS